Clinical and laboratory features of acute intestinal infections with hyemocolitis syndrome in children - O. I. Klimova; N. V. Gonchar; L. A. Alekseeva; Yu. V. Lobzin (Журнал инфектологии, 2019)
The acute intestinal infections (AII) with a haemocolitis syndrome represent group of a serious illness at children that defines relevance of studying of their etiology and pathogenesis. The purpose of the work is to study the clinical and laboratory features of AII with hemocolitis syndrome depending on the etiology and complications. Materials and methods. Observed 77 patients of AII aged from 3 months up to 16 years. The etiological diagnosis verified using bacteriological and PCR studies of feces with AmpliSens® OKA screen-FL reagents and serological methods. Hemocolitis syndrome was observed in all patients. Patients with AII of a clarified etiology formed group 1 (n = 59), with AII of unclarified etiology – group 2 (n = 18). Intercurrent diseases were detected as non-specific complications of acute intestinal infections: respiratory (RI) and urinary infections (UI). AII severity was determined by the Clarke-index, the severity of dehydration – according to the WHO clinical scale. To evaluate the data of a research, the Mann-Whitney U-test and Pearson correlation coefficients were used. Results. There was a difference in the age of children in group 1 (3.9 ± 4.2 g) and group 2 (2.2 ± 2.6 g; p = 0.03) and in the frequency of complications: RI is diagnosed in group 1 for 54.5% of children, in group 2 for 83.3% (p=0.001); UI – at 45.5% and 16.7% respectively (p=0.03). In complicated course of AII, macroscopic signs of hemocolitis and inflammatory changes in the hemogram with the inclusion of platelet hemostasis in group 1 observed significantly more often than in group 2. In children of group 1, with uncomplicated acute intestinal infections, there was a significant correlation of signs of inflammation with dehydration and a higher severity of the disease according to the Clarke-index than with a complicated course. Conclusion. The age of children with AII of a clarified etiology was 3.9 ± 0.6 years, with AII of an unclarified etiology – 2.2 ± 0.6 years. AII of a clarified etiology preceded more hard, than AII of unclarified etiology. Complicated course of AII with hemocolitis syndrome characterized by expressiveness of signs of the local and system inflammatory answer.